A Proposed Shariah Compliant Fintech Model as An Alternative Fi-nancing Product to Tackle Food Security Challenges in Malaysia - Hassan Azganin; Salina Bt. Kassim; Auwal Adam Sa’ad (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
Ensuring food security becomes a significant issue in many countries, particularly during the coronavirus pandemic. Thus, the agriculture sector’s development is critically essential to improving food availability. Despite several initiatives launched by the Malaysian authorities to support small farmers, this sector continues to suffer from accessing financial services. This paper objective is to develop a shariah based financing alternative model known as the Shariah-Compliant Fintech (SCF) Model. This model incorporates crowdfunding solutions and smart contracts into one platform to provide a seamless experience for the investors and fund seekers. This paper starts with the conceptual exploration of the literature in the areas of food security, financing challenges facing farmers, smart contract and Crowdfunding application. The sources of the literature cover secondary sources such as books, online resources and journal articles. This paper provides a conceptual framework of the shariah compliant fintech model that could be a viable solution for the global crowd investors to participate in the impactful investment opportunities. Second, the platform represents a marketplace for small farmers to seek financing from alternative sources of funds for their agricultural projects. This study offers a comprehensive shariah investment procedure and structures of the fintech industry, which can assist policymakers to create necessary policies that regulate Crowdfunding and smart contracts activities. Keywords: Food Security, Fintech, Shariah Compliance, Crowdfunding, Smart Contracts